UNVEILING THE FINNISH EDUCATION SYSTEM: A MODEL OF EXCELLENCE - Safaraliyev Chingiz Olim o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The Finnish education system has garnered global admiration for its consistently high performance in international assessments and its holistic approach to education. This article delves into the key components that underpin Finland's educational success, examining its unique pedagogical strategies, teacher training programs, curriculum design, and equitable practices. By exploring these facets, we aim to uncover valuable insights that can inform educational policies and practices worldwide.